Essays in Quantitative Macroeconomics - Palmer, Thomas Mark (My University, 2024)
This thesis comprises three papers in quantitative macroeconomics that explore the following questions: (1) How does employer-provided training impact the college wage premium in the context of skill-biased technological change? (2) How does the option to sell a firm influence firm entry, exit, and growth dynamics? (3) How does college major selection impact occupational sorting and entrepreneurship? Chapter 1 combines matched employer-employee survey data from Canada with a quantitative model of the labour market featuring endogenous technology and training decisions to show that the rise in training, driven by technological advancements, attenuated the increase in the college wage premium by 63 percent between 1980 and the early 2000s. Chapter 2, co-authored with Bettina Brueggemann and Zachary Mahone, uses administrative matched employer-employee data from Canada and a quantitative model of firm dynamics to establish that transfers of business ownership significantly impact firm entry, exit, and growth dynamics, with 13 percent of new entrants surviving solely due to the option value of sale. Chapter 3 empirically establishes a negative relationship between STEM majors and entrepreneurship using micro-data from the 1997 National Longitudinal Survey of Youth. Through a quantitative model that links decisions regarding majors and entrepreneurship, I show that lowering STEM tuition increases STEM enrolment at the cost of reducing overall entrepreneurial activity.
Keywords: Macroeconomics; Labour Economics; Economics; Education; Training; Entrepreneurship; Firm Dynamics; Inequality